Effects of group guidance activities on students' self-concept - Mohamad Yusop, Yusni; Zainudin, Zaida Nor; Ismail, Asmah (Human Resource Management Academic Research Society, 2018)
This study is to identify the enhancement of students’ self-concept through the implementation of group guidance. A group guidance activity was conducted in accordance with the group guidance structured activities, aiming to improve the self-concept of primary school students. A total of 64 fifth year students were selected for this study through simple random sampling. They were randomly assigned to a treatment group (n = 31) and a control group (n = 33). Both groups were given the Tennessee Self-Concept Children:2 (TSCS: 2) to measure their level of self-concept before and after the intervention. The experimental group went through a seven-week group guidance module with two sessions per week. Analysis shows that there is a significant difference in the mean score of the self-concept of post-intervention between the treatment group and the control group. The implementation of group guidance has helped to improve the self-concept of primary school children through adaptive activities.